Development of a Mobile Driving Simulator to Eliminate False Motion Cues - Abdullah, M.; Koetniyom, S.; Carmai, J. (Journal of the Society of Automotive Engineers Malaysia, 2021)
Driving Simulators are a valuable tool for the evaluation of driver assistance systems and analysis of user behaviour. They consist of a vehicle mock-up and a display, motion and an audio system. As, driving is mainly a visual task and the driver receives most of the information through his eyes, so the configuration of the display is very important for accurate perception of surroundings. Important features of a display system are its distance from driver’s eyes, field of view, continuity and the picture quality of the displayed image. In order to simulate motion, most of the existing driving simulators consist of a dome, mounted on a Stewart platform, which is either stationary or moves on a rail or a horizontal table. Due to the limiting working space of the motion system of such driving simulators, they cannot accurately simulate longitudinal accelerations so they use scaled vehicle dynamics model or blend the longitudinal movement of simulator with the tilt movement, which the driver perceives as unrealistic motion cues. To eliminate the issues of false motion perception in the driver, a mobile driving simulator is developed, which is to be driven on a planar area and a display system is designed around it. The display system covers the horizontal and vertical field of view of the driver and the distance of the display system from the driver’s eyes is chosen in such a way that it takes into account the accommodation effects, which helps in the perception of depth. This results in a display system in the form of 220º cylindrical dome with a diameter of approximately 4.8 meter.